Effects of aerobic exercise combined with resistance training on body composition and metabolic health in children and adolescents with overweight or obesity: systematic review and meta-analysis - Liu, Xuan; Li, Qiang; Lu, FuXiang; Zhu, Dongsheng (Frontiers in Public Health, 2024)
Background To systematically review the effects of aerobic exercise and resistance training on Metabolic Health in children and adolescents with overweight/obesity. Methods Employing a retrieval strategy that combines subject terms and free terms, searches were conducted in the CNKI, WanFangData, VIP, PubMed, Web of Science, Embase, and Cochrane Library databases up to October 31, 2023. Results A total of 29 studies involving 2,195 subjects were included. The combination of aerobic and resistance training significantly reduces body composition and metabolic health in children and adolescents with overweight or obesity, as evidenced by changes in various parameters (BMI, WC, FM, BF%, VO2max, TG, TC, HDL-C, LDL-C, HOMA-IR, FPG, INS). However, there were no significant differences observed in hs-CRP. Subgroup analyses further showed that changes in intervention measurement had a significant effect on the effectiveness of the intervention. Conclusion Aerobic exercise combined with resistance training has a positive impact on the physical health of children and adolescents with overweight/obesity. The recommended exercise prescription is at least three sessions of more than 60 min per week for 12 weeks or more for better health benefits.